Model for clipping‐induced timing error of bandwidth‐limited comparators. Issue 8 (1st April 2013) - Ritter, P.; Le Tual, S.; Allard, B.; Möller, M.
Abstract : A comparator timing error model is presented for comparators with a limiting transfer characteristic and a first‐order lowpass behaviour. It shows that the delay from the reference crossing at the input to the zero crossing at the output deviates from the lowpass phase shift if the signal amplitude exceeds the comparator linearity range (clipping). This deviation is a timing error since it varies nonlinearly with the signal amplitude, the signal frequency and the reference level and may cause significant distortion in the comparator application. Evaluation of the timing error shows that generally a signum function transfer characteristic is inappropriate for timing critical applications, e.g. analogue‐to‐digital converters, unless the lowpass bandwidth is multiple times higher than the signal frequency.